2017
DOI: 10.1155/2017/7605893
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rumination and Stressful Life Events in the Relationship between the Qi Stagnation Constitution and Depression in Women: A Moderated Mediation Model

Abstract: The qi stagnation constitution is associated with depression in traditional Chinese medicine. It is unclear how rumination and stressful life events affect the relationship between the qi stagnation constitution and depression. The Qi Stagnation Constitution Scale, Ruminative Response Scale, Center for Epidemiologic Studies Depression Scale, and Adolescent Self-Rating Life Events Checklist were used to assess this association in 1200 female college students. The results revealed that the qi stagnation constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…The RRS is composed of three dimensions, which are brooding, reflection, and depression-related. The Chinese version of RRS has been widely used and has reported good reliability and validity among Chinese college students (41). In this study, the Cronbach’s alpha of the RRS was 0.81 for the whole scale.…”
Section: Methodsmentioning
confidence: 99%
“…The RRS is composed of three dimensions, which are brooding, reflection, and depression-related. The Chinese version of RRS has been widely used and has reported good reliability and validity among Chinese college students (41). In this study, the Cronbach’s alpha of the RRS was 0.81 for the whole scale.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, it has been shown that the relationship between negative emotions and creativity may be influenced by an individual’s internal psychological environment, such as their level of rumination ( Verhaeghen et al, 2005 ; Cohen and Ferrari, 2010 ). What is more, rumination has served as a mediator and moderator in studies related to negative emotions such as anxiety and depression ( Liu et al, 2017 ). However, there is a paucity of research on how rumination is associated with depression, psychological resilience and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…These people are susceptible to skin eruptions, drug allergies, asthma, seasonal changes, and other environmental allergens [24]. A larger proportion of unbalanced body constitution types have been found in patients who suffered from depression than those with a balanced body constitution [23,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…People with the qi dynamic disturbed in their body are categorized as QSC; they are mostly thin and tend to be suspicious [ 20 ]. They also respond to stressful situations poorly [ 23 ]. Next, people with BSC are often forgetful and impatient [ 20 ].…”
Section: Introductionmentioning
confidence: 99%